Knowledge in open innovation process on an example of pharmaceutical industry - Pohulak-Żołędowska, Elżbieta; Żabiński, Arkadiusz; Sosnowski, Michał (Wykorzystanie wiedzy w otwartym procesie innowacyjnym na przykładzie przemysłu farmaceutycznego, 2017)
The innovation models develop over time, due to market and industry needs. As the main “product” of knowledge economy, innovations (as a concept) are symbolic goods, founded in symbols, not in atoms. This notion causes some consequences typical for information goods, like ease of replication or exchange, zero-marginal replication costs and cheap storage. On the other hand, there is a growing innovation production cost and uncertainty and risk of innovation activity that discourage companies from being innovative. Open innovation model shows the knowledge flows in the “inner” and “outer” sphere of the innovation process. The knowledge has been showed in some aspects: as private good, public good and also as “the commons”. The transition spheres have been showed too. Opening the innovation process is addressed to the costly and risky projects that cause risk aversion amongst entrepreneurs, but without which useful products might have never been produced. The goal of the article is to show the knowledge flow and knowledge transition between innovation actors, its “common” nature and the trial to show the value added in the open innovation process. Methods used are literature and data analysis as well as case study
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 489, s. 274-289
Keywords: the commons; open innovation; knowledge; innovation process; dobra wspólne; innowacje otwarte; wiedza; proces innowacyjny